Workshop Mengasah Keterampilan Berpikir Kritis: Membangun Generasi Pariwisata Yang Kreatif Dan Analitis Di SMKS Efata Omba Rade - Janga, Adelbertus Umbu; Setiawi, Agustina Purnami; Sabawaly, Diana Reby; Mau, Stefanus Dwi Istiavan (CV. Global Cendekia Inti, 2024)
This workshop aims to enhance the critical thinking skills of teachers at SMKS Efata Omba Rade to effectively support the implementation of the Merdeka Curriculum. The main focus of this activity is to develop the teachers' non-technical or soft skills, particularly in critical thinking and contextual pedagogy. The three primary objectives of this workshop include: (1) increasing teachers' understanding of critical thinking skills in implementing the Merdeka Curriculum, (2) strengthening pedagogical skills to support more contextual and meaningful teaching methods, and (3) guiding teachers in training students to think critically within the context of the tourism industry. This workshop is expected to enrich teachers' ability to apply innovative and effective teaching methods. The anticipated outcomes include enhanced critical thinking skills for teachers, a deep understanding of pedagogy relevant to industry demands, and teacher readiness to guide students toward becoming a creative and analytical generation. Thus, this activity contributes to preparing SMKS Efata graduates to face challenges and opportunities in the workforce, particularly in the tourism sector